The Effect of Using Poster Media (الوسيلة الملصقة) on Students' Speaking Skill - Syahrul Ayup; Zikra Wahyuni Maiza (Journal of English Language and Education, 2022)
The purpose of this study is to determine the effect of using poster media on students' speaking skills at the H. Muhammad Djana Lubis Islamic Boarding School Modern Islamic School Foundation, Cubadak. This research using poster media is expected to provide benefits to teachers and students in carrying out teaching and learning activities, especially in improving Arabic speaking skills. The method used in this research is an experimental method using two class groups. One class as the experimental class and one class for the control. the researcher delivered the learning material using poster media in the experimental class, while in the control class where the learning material was delivered by the lecture method. Based on the results of the analysis in the previous discussion, it was stated that the students' scores in the experimental class were superior to the control class. The average score obtained by students in the experimental class using poster media is 85.5 and the average score in the control class without the latest media assistance is 80.5. Using poster as media has significant effect on the students’ Arabic speaking skill.